Efficacy of Quadratus Lumborum Block in Children with Laparoscopic-Assisted Pyeloplasty - Gözen Öksüz; Ahmet Burak Doğan (Erciyes Medical Journal, 2019)
Objective: The quadratus lumborum block (QLB) is a new and effective truncal block used for postoperative analgesia in patients undergoing upper and lower abdominal surgeries. We aimed to evaluate and compare the efficacy of QLB and wound infiltration (WI) using postoperative Face, Legs, Activity, Cry, and Consolability (FLACC) pain scores and total 24-h analgesic consumption in pediatric patients who underwent laparoscopic-assisted pyeloplasty (LAP). Materials and Methods: Patients who underwent LAP between May 2016 and June 2017 were retrospectively examined and were divided into two groups: QLB group and WI group. Patients' FLACC scores at 1, 6, 12, and 24 h; postoperative analgesic doses; and complications were evaluated from patient's records. Results: A total of 31 patients who underwent LAP were identified from the records. Of them, 14 had QLB and 17 had WI. Demographic characteristics of patients and operation duration were similar between the two groups. FLACC scores at 1, 6, 12, and 24 h and postoperative total 24-h paracetamol consumption were significantly lower in the QLB group. No complications were seen in both groups. Conclusion: According to the present study results, QLB provides a longer and more effective postoperative analgesia than WI in pediatric patients who have undergone LAP.